A Long-Distance Translocatable Phloem Protein from Cucumber Forms a Ribonucleoprotein Complex In Vivo with Hop Stunt Viroid RNA - Gómez, Gustavo (American Society for Microbiology, 2004)
Viroids are highly structured plant pathogenic RNAs that do not code for any protein, and thus, their long-distance movement within the plant must be mediated by direct interaction with cellular factors, the nature of which is presently unknown. In addition to this type of RNAs, recent evidence indicates that endogenous RNAs move through the phloem acting as macromolecular signals involved in plant defense and development. The form in which these RNA molecules are transported to distal parts of the plant is unclear. Viroids can be a good model system to try to identify translocatable proteins that could assist the vascular movement of RNA molecules. Here, we demonstrate by use of immunoprecipitation experiments, that the phloem protein 2 from cucumber (CsPP2) is able to interact in vivo with a viroid RNA. Intergeneric graft assays revealed that both the CsPP2 and the Hop stunt viroid RNA were translocated to the scion. The translocated viroid is symptomatic in the nonhost scion, indicating that the translocated RNA is functional. The CsPP2 gene was cloned and sequenced. The analysis of its primary structure revealed the existence of a potential double-spaced-RNA-binding motif, previously identified in a set of proteins that bind to highly structured RNAs, which could explain its RNA-binding properties. The possible involvement of this phloem protein in assisting the long-distance movement of the viroid RNA within the plant is discussed.